Oil stock discovery and Dutch disease - Kirk Hamilton; John Hartwick (Queen's University, Department of Economics, 2008)
We set out a model of a small open economy exporting oil and a traditional exportable in return for produced capital. The small open economy also has local production of a non-traded good. We first observe that the size of the traditional export sector declines with an exogenous increase in the country's oil stock. Strong Dutch disease (SDD) involves a net diminution in produced capital in use in the small open economy after the oil discovery shock. SDD turns on the exportable sector being relatively capital intensive.
Keywords: F43; Q32; Q33; 330; dutch disease; resource discovery; invariant earnings; Kleines-offenes-Land; Exportindustrie; Erdölvorkommen; Erdölförderung; Einkommen; Dutch Disease